Five-year alendronate treatment outcome in older postmenopausal Japanese women with osteoporosis or osteopenia and clinical risk factors for fractures - Jun Iwamoto; Atsushi Miyata; Yoshihiro Sato; et al (Dove Medical Press, 2009)
Jun Iwamoto1, Atsushi Miyata2, Yoshihiro Sato3, Tsuyoshi Takeda1, Hideo Matsumoto11Institute for Integrated Sports Medicine, Keio University School of Medicine, Tokyo, Japan; 2Department of Internal Medicine, Yahata Clinic, Tokyo, Japan; 3Department of Neurology, Mitate Hospital, Fukuoka, JapanAbstract: A retrospective study was conducted to evaluate the outcome of treatment with alendronate (ALN) for 5 years in postmenopausal Japanese women with an increased risk of fractures. Forty postmenopausal Japanese women with osteoporosis or osteopenia and clinical risk factors for fractures (mean age: 75.4 years) were analyzed; 33 patients were treated with alendronate and 7 were treated with alfacalcidol (ALF, controls) in an outpatient clinic run by general practitioners. The metacarpal bone mineral density (BMD) measured using a computed X-ray densitometer, urinary levels of cross-linked N-terminal telopeptides of type I collagen (NTX), and serum levels of alkaline phosphatase (ALP) were monitored during the 5-year treatment period. The urinary NTX and serum ALP levels decreased significantly in the ALN group, compared with the ALF group. The metacarpal BMD was sustained in the ALN group but decreased significantly in the ALF group; the difference between these two groups was also significant. The present study evaluated the outcome of treatment with ALN for 5 years in postmenopausal Japanese women with osteoporosis or osteopenia and clinical risk factors for fractures. ALN successfully suppressed bone turnover and sustained the metacarpal BMD over the 5-year period of treatment in postmenopausal Japanese women with an increased risk of fractures.Keywords: alendronate, osteoporosis, osteopenia, risk factors for fractures, postmenopausal women